A new species and new records of Tinus F. O. Pickard-Cambridge, 1901 (Araneae: Pisauridae) - Cruz Da Silva, Estevam L. (Zootaxa, 2012)
The spider genus Tinus F. O. Pickard-Cambridge, 1901 was revised by Carico (1976) and currently comprises nine species distributed from Mexico to Panama (Platnick, 2012). The most recently described species is Tinus oaxaca Carico, 2008, based on a single male from Mexico (Carico 2008). In this work a new species of Tinus is described and illustrated for the first time.